Deconstruction of Ecofeminist Ideology in Japanese Eco-friendly Beauty Products Advertisements - Sari, Ida Ayu Laksmita; Mahardika, I Gusti Ayu Sugiartini (Institut Seni Indonesia Denpasar, 2024)
Nowadays, many advertisements for Japanese cosmetic products are appearing that show ecology issues. Ecology issues and the role of women shown in advertisements cause the meaning to develop and become a deconstruction of previous advertisements. Now, the ideology contained in an advertisement can contain ecology issues and women's involvement in it or is called ecofeminist ideology. This research seeks to the forms of deconstruction of ecofeminist ideology. This research is qualitative research using document study methods and netnography methods. Data was collected from eight advertisements, then analyzed using Derrida's deconstruction theory, Barthes' semiotics, and Vandana Shiva’s ecofeminism theory. The results of this research show the forms of deconstruction of ecofeminist ideology in advertising are (1) represented by the role of women and efforts to save the future of nature, (2) nature and women grow together, (3) women's beauty is natural beauty, (4) and the relationship of tsubaki cultivation, traditions and women farmers.